Functional prediction of tomato PLATZ family members and functional verification of SlPLATZ17 - Min Xu; Zhao Gao; Dalong Li; Chen Zhang; Yuqi Zhang; Qian He; Yingbin Qi; He Zhang; Jingbin Jiang; Xiangyang Xu; Tingting Zhao (Journal of Integrative Agriculture, 2024)
PLATZ is a novel zinc finger DNA-binding protein that plays an important role in regulating plant growth and development and resisting abiotic stress. However, there has been very little research on the function of this family gene in tomatoes, which limits its application in germplasm resource improvement. Therefore, the PLATZ gene family was identified and analyzed in tomato, and its roles were predicted and verified to provide a basis for in-depth research on SlPLATZ gene function. In this study, the PLATZ family members of tomato were identified in the whole genome, and 19 SlPLATZ genes were obtained. Functional prediction was conducted based on gene and promoter structure analysis and RNA-seq-based expression pattern analysis. SlPLATZ genes that responded significantly under different abiotic stresses or were significantly differentially expressed among multiple tissues were screened as functional gene resources. SlPLATZ17 was selected for functional verification by experiment-based analysis. The results showed that the downregulation of SlPLATZ17 gene expression reduced the drought and salt tolerance of tomato plants. Tomato plants overexpressing SlPLATZ17 had larger flower sizes and long, thin petals, adjacent petals were not connected at the base, and the stamen circumference was smaller. This study contributes to understanding the functions of the SlPLATZ family in tomato and provides a reference for functional gene screening.